FAP Promotes Immunosuppression by Cancer-Associated Fibroblasts in the Tumor Microenvironment via STAT3-CCL2 Signaling - Yang, Xuguang; Lin, Yuli; Shi, Yinghong; Li, Bingji; Liu, Weiren; Yin, Wei; Dang, Yongjun; Chu, Yiwei; Fan, Jia; He, Rui (Cancer research (Chicago, Ill.), 2016)
Cancer-associated fibroblasts (CAF) are components of the tumor microenvironment whose contributions to malignant progression are not fully understood. Here, we show that the fibroblast activation protein (FAP) triggers induction of a CAF subset with an inflammatory phenotype directed by STAT3 activation and inflammation-associated expression signature marked by CCL2 upregulation. Enforcing FAP expression in normal fibroblasts was sufficient to endow them with an inflammatory phenotype similar to FAP(+)CAFs. We identified FAP as a persistent activator of fibroblastic STAT3 through a uPAR-dependent FAK-Src-JAK2 signaling pathway. In a murine liver tumor model, we found that FAP(+)CAFs were a major source of CCL2 and that fibroblastic STAT3-CCL2 signaling in this setting promoted tumor growth by enhancing recruitment of myeloid-derived suppressor cells (MDSC). The CCL2 receptor CCR2 was expressed on circulating MDSCs in tumor-bearing subjects and FAP(+)CAF-mediated tumor promotion and MDSC recruitment was abrogated in Ccr2-deficient mice. Clinically, we observed a positive correlation between stromal expression of FAP, p-STAT3, and CCL2 in human intrahepatic cholangiocarcinoma, a highly aggressive liver cancer with dense desmoplastic stroma, where elevated levels of stromal FAP predicted a poor survival outcome. Taken together, our results showed how FAP-STAT3-CCL2 signaling in CAFs was sufficient to program an inflammatory component of the tumor microenvironment, which may have particular significance in desmoplasia-associated cancers. Cancer Res; 76(14); 4124-35. ©2016 AACR.